Investigating the contributions of herbaceous vegetation biomass to soil accretion in Louisiana's coastal deltaic wetlands using airborne imaging spectroscopy - Daniel Jensen; Elena Solohin; Edward Castañeda-Moya; Marc Simard; David R. Thompson; Cathleen E. Jones; Alexandra Christensen; Andre Rovai; Andy Fontenot; Robert Twilley (Remote Sensing of Environment, 2026)

Delta-X: An airborne remote sensing framework to calibrate hydrodynamic and ecogeomorphic processes responsible for land building in coastal deltas - Marc Simard; Cathleen E. Jones; Robert R. Twilley; Edward Castañeda-Moya; Sergio Fagherazzi; Cédric G. Fichot; Michael P. Lamb; Paola Passalacqua; Tamlin M. Pavelsky; David R. Thompson; Saoussen Belhadj-aissa; Pradipta Biswas; et al. (Remote Sensing of Environment, 2026)

Mapping salt marsh hydroperiod using Synthetic Aperture Radar time series - Saoussen Belhadj-aissa; Marc Simard; Adriana Parra Ruiz; Jordi Palacios; Sergio Fagherazzi (Remote Sensing Applications: Society and Environment, 2026)

Examining the status of mangrove forest dynamics and community-led management on the Colombian Pacific coast - Paulo J. Murillo-Sandoval; Mauricio Perea-Ardila; Marc Simard (Ocean & Coastal Management, 2025)

A hyperspectral view of the nearshore Mississippi River Delta: Characterizing suspended particles in coastal wetlands using imaging spectroscopy - Joshua P. Harringmeyer; Nilotpal Ghosh; Matthew W. Weiser; David R. Thompson; Marc Simard; Steven E. Lohrenz; Cédric G. Fichot (Remote Sensing of Environment, 2024)

Observation of the Coastal Areas, Estuaries and Deltas from Space - Benoit Laignel; Stefano Vignudelli; Rafael Almar; Mélanie Becker; Abderrahim Bentamy; Jérôme Benveniste; Florence Birol; Frédéric Frappart; Deborah Idier; Edward Salameh; Marcello Passaro; Melisa Menende; et al. (Surveys in Geophysics, 2023)
Coastal regions (including estuaries and deltas) are very complex environments with diverse hydrodynamic and bio-geomorphological contexts and with important socio-economic and ecological problems. These systems are among the most affected by human impact through urbanization and port activities, industrial and tourism activities. They are directly affected by the impact of climate change on sea level, storm surges frequency and strength, as well as recurrence of coastal river floods. A sustainable future for coastal zones depends on our capacity to implement systematic monitoring with focus on: (1) forcings affecting coastal zones at different spatio-temporal scales (sea level rise, winds and waves, offshore and coastal currents, tides, storm surges, river runoff in estuaries and deltas, sediment supply and transport, vertical land motions and land use); (2) morphological response (e.g., shoreline migration, topographical changes). Over the last decades, remote sensing observations have contributed to major advances in our understanding of coastal dynamics. This paper provides an overview of these major advances to measure the main physical parameters for monitoring the coastal, estuarine and delta environments and their evolution, such as the water level and hydrodynamics near the shoreline, water/sediment contact (i.e., shoreline), shoreline position, topography, bathymetry, vertical land motion, bio-physical characteristics of sediments, water content, suspended sediment, vegetation, and land use and land cover.

A regional map of mangrove extent for Myanmar, Thailand, and Cambodia shows losses of 44% by 1996 - Priscilla Baltezar; Paulo J. Murillo-Sandoval; Kyle C. Cavanaugh; Cheryl Doughty; David Lagomasino; Thida Tieng; Marc Simard; Temilola Fatoyinbo (Frontiers in Marine Science, 2023)
Southeast Asia is home to some of the planet’s most carbon-dense and biodiverse mangrove ecosystems. There is still much uncertainty with regards to the timing and magnitude of changes in mangrove cover over the past 50 years. While there are several regional to global maps of mangrove extent in Southeast Asia over the past two decades, data prior to the mid-1990s is limited due to the scarcity of Earth Observation (EO) data of sufficient quality and the historical limitations to publicly available EO. Due to this literature gap and research demand in Southeast Asia, we conducted a classification of mangrove extent using Landsat 1-2 MSS Tier 2 data from 1972 to 1977 for three Southeast Asian countries: Myanmar, Thailand, and Cambodia. Mangrove extent land cover maps were generated using a Random Forest machine learning algorithm that effectively mapped a total of 15,420.51 km 2 . Accuracy assessments indicated that the classification for the mangrove and non-mangrove class had a producer’s accuracy of 80% and 98% user’s accuracy of 90% and 96%, and an overall accuracy of 95%. We found a decline of 6,830 km 2 between the 1970s and 2020, showing that 44% of the mangrove area in these countries has been lost in the past 48 years. Most of this loss occurred between the 1970s and 1996; rates of deforestation declined dramatically after 1996. This study also elaborated on the nature of mangrove change within the context of the social and political ecology of each case study country. We urge the remote sensing community to empathetically consider the local need of those who depend on mangrove resources when discussing mangrove loss drivers.

Mangroves Cover Change Trajectories 1984-2020: The Gradual Decrease of Mangroves in Colombia - Paulo J. Murillo-Sandoval; Lola Fatoyinbo; Marc Simard (Frontiers in Marine Science, 2022)
Awareness of the significant benefits of mangroves to human lives and their role in regulating environmental processes has increased during the recent decades. Yet there remains significant uncertainty about the mangrove change trajectories and the drivers of change at national scales. In Colombia, the absence of historical satellite imagery and persistent cloud cover have impeded the accurate mapping of mangrove extent and change over time. We create a temporally consistent Landsat-derived dataset using the LandTrendr algorithm to track the historical land cover and mangrove conversion from 1984-2020 across Colombia. Over this period, mangrove extent decreased by ~48.000ha (14% of total mangrove area). We find a gradual reduction of mangrove extent along the Pacific coast since 2004, whereas, in the Caribbean, mangrove cover declined around during 1984-1988 and also after 2012. Our time-series analysis matches with drivers of mangrove change at three local sites. For instance, hydroclimatic events, dredging activities, and high sediment loads transported by the rivers have collectively improved mangrove recovery in some sites. In contrast, human activities pressure linked to agricultural expansion and road construction have degraded mangroves. The transition from dense mangrove to other vegetation types is the most significant conversion affecting mangrove cover in Colombia, impacting an area of 38,469 ± 2,829 ha. We anticipate increased mangrove loss, especially along the Pacific coast, resulting from intensified human activity. Prioritization of conservation areas is needed to support local institutions, maintain currently protected areas, and develop strategies (e.g. payment for ecosystem services) to preserve one of the most pristine mangrove regions in the Western Hemisphere.

Application of the metabolic scaling theory and water–energy balance equation to model large‐scale patterns of maximum forest canopy height - Sungho Choi; Christopher P. Kempes; Taejin Park; Sangram Ganguly; Weile Wang; Liang Xu; Saikat Basu; Jennifer L. Dungan; Marc Simard; Sassan S. Saatchi; Shilong Piao; Xiliang Ni; et al. (Global Ecology and Biogeography, 2016)
Aim Forest height, an important biophysical property, underlies the distribution of carbon stocks across scales. Because in situ observations are labour intensive and thus impractical for large‐scale mapping and monitoring of forest heights, most previous studies adopted statistical approaches to help alleviate measured data discontinuity in space and time. Here, we document an improved modelling approach which links metabolic scaling theory and the water–energy balance equation with actual observations in order to produce large‐scale patterns of forest heights. Methods Our model, called allometric scaling and resource limitations (ASRL), accounts for the size‐dependent metabolism of trees whose maximum growth is constrained by local resource availability. Geospatial predictors used in the model are altitude and monthly precipitation, solar radiation, temperature, vapour pressure and wind speed. Disturbance history (i.e. stand age) is also incorporated to estimate contemporary forest heights. Results This study provides a baseline map ( c . 2005; 1‐km 2 grids) of forest heights over the contiguous United States. The Pacific Northwest/California is predicted as the most favourable region for hosting large trees ( c . 100 m) because of sufficient annual precipitation (> 1400 mm), moderate solar radiation ( c . 330 W m −2 ) and temperature ( c . 14 °C). Our results at sub‐regional level are generally in good and statistically significant ( P ‐value Main conclusions We improved the metabolic scaling theory to address variations in vertical forest structure due to ecoregion and plant functional type. A clear mechanistic understanding embedded within the model allowed synergistic combinations between actual observations and multiple geopredictors in forest height mapping. This approach shows potential for prognostic applications, unlike previous statistical approaches.

An approach to monitoring mangrove extents through time-series comparison of JERS-1 SAR and ALOS PALSAR data - Nathan Thomas; Richard Lucas; Takuya Itoh; Marc Simard; Lola Fatoyinbo; Peter Bunting; Ake Rosenqvist (Wetlands Ecology and Management, 2015)

Disruption of Ion Homeostasis in the Neurogliovascular Unit Underlies the Pathogenesis of Ischemic Cerebral Edema - Arjun Khanna; Kristopher T. Kahle; Brian P. Walcott; Volodymyr Gerzanich; J. Marc Simard (Translational Stroke Research, 2014)

Height and biomass of mangroves in Africa from ICESat/GLAS and SRTM - Temilola E. Fatoyinbo; Marc Simard (International Journal of Remote Sensing, 2013)

Transient receptor potential melastatin 4 and cell death - J. Marc Simard; S. Kyoon Woo; Volodymyr Gerzanich (Pflügers Archiv - European Journal of Physiology, 2012)

Heparin Reduces Neuroinflammation and Transsynaptic Neuronal Apoptosis in a Model of Subarachnoid Hemorrhage - J. Marc Simard; Cigdem Tosun; Svetlana Ivanova; David B. Kurland; Caron Hong; Leanne Radecki; Carter Gisriel; Rupal Mehta; David Schreibman; Volodymyr Gerzanich (Translational Stroke Research, 2012)

Glibenclamide—10-h Treatment Window in a Clinically Relevant Model of Stroke - J. Marc Simard; Seung Kyoon Woo; Natalia Tsymbalyuk; Oksana Voloshyn; Vladimir Yurovsky; Svetlana Ivanova; Ryan Lee; Volodymyr Gerzanich (Translational Stroke Research, 2012)

Targeting the Microvasculature in Cerebral Ischemia—Go (or Stop Going) with the Flow - J. Marc Simard; Volodymyr Gerzanich (Translational Stroke Research, 2011)

Inflammation of the Choroid Plexus and Ependymal Layer of the Ventricle Following Intraventricular Hemorrhage - Philippe F. Simard; Cigdem Tosun; Ludmila Melnichenko; Svetlana Ivanova; Volodymyr Gerzanich; J. Marc Simard (Translational Stroke Research, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)